Tradisi Appanaung: Menjaga Keharmonisan Keluarga dan Kelestarian Makam Kuno - nfn Makmur (Tumotowa, 2020)
The Appanaung tradition is a tradition that must be done by the community in Kampung Sikapaya of Minasa Upa village Bontoa District of Maros District. This research aims to determine the process of implementation and impact that is produced by appanaung tradition, especially in the preservation aspects of the culture of material (ancient tomb). So it can give an idea of how the cultural function of oral tradition in the community. In the achievement of using ethnoarchaeological methods, namely the merging of methods archeology and anthropology. To acquire cultural data the appanaung tradition using observations involved (observation participatory) and in-depth interviews with people who carry out the appanaung tradition and the community in Kampung Sikapaya. Meanwhile, in obtaining material cultural data by observing, noting, capturing, and photographing ancient tomb building findings with proximity, thus obtaining archaeological data in the context and surrounding environment. The results of the study of the appanaung tradition in Kampung Sikapaya must be done by everyone and held after the marriage. This tradition is believed by society to function as a reinforcement for the new household. The harmonization of the new household can be realized after obtaining the blessing from the ancestors so that the peak of the appanaung tradition was held in ancient tombs. From the appanaung tradition that led and mobilized the community to preserve the ancient tombs.